Delayed access to treatment and frequency of acute respiratory infection as risk factors of severe pneumonia among children aged 12-59 months in Denpasar, Bali - Dewa Ayu Ketut Sri Abadi; Dewa Nyoman Wirawan; Anak Agung Sagung Sawitri; I Gusti Ayu Trisna Windiani (Universitas Udayana, 2017)
Background and purpose: Period prevalence of pneumonia among children in Indonesia increased from 2.1 in 2007 to 2.7 per 1000 children in 2013. The highest incidence was found among children aged 12-23 months. This study aims to examine association between delayed access to health care facilities and severity of children pneumonia. Methods: A case control study was conducted in Denpasar City. A total of 132 children were recruited to participate in this study, consisted of 44 cases and 88 controls. Cases were selected from 161 children with severe pneumonia who registered at Pulmonology Department of Sanglah General Hospital between January 2015 and April 2016. Controls were selected from 261 children aged 12-59 months with mild pneumonia who visited out-patient service at all community health centres in Denpasar City between January 2015 and April 2016. Cases and controls were matched by sex. Data were collected by interview with the parents in their houses. Data were analysed using multivariate analysis with logistic regression. Results: Risk factors associated to severity of pneumonia among children aged 12-59 months were delayed access to treatment for more than three days (AOR=2.15;95%CI: 1.39-3.32), non-health care facilities at first episode of illness (AOR=4.02; 95%CI: 1.53-10.61) and frequent episodes of respiratory infections (>4 times) over the last 6 months (AOR=5.45; 95%CI: 2.13-13.96). Conclusion: Delayed access to treatment, did not access healthcare facilities at first episode of illness, and high frequency of acute respiratory infections are risk factors of severe pneumonia among children.